HIDROLISIS GUGUS METOKSIL PEKTIN AMPAS TEBU UNTUK MENGHASILKAN BIOMETANOL - Akyunul Jannah; Arief Suryadinata (SAINSTIS, 2012)
Methanol is a potential in two areas, namely as fuel cells and biodiesel. Among the many biomass, pectin is one of the best for the production of methanol. The purpose of this study was to determine the influence of pectin methyl esterase enzyme  concentration  (PME)  group  metoksil  rough  on  pectin  hydrolysis  of bagasse to produce the highest levels of biometanol. Methods This study includes the preparation of the bagasse, further hydrolysis using crude extract of the enzyme pectin methyl esterase (PMEs) resulting from bacterial culture Bacillus subtilis at Borth Nutrient media (NB) with 1% pectin. Hydrolysis of Metoksil groups of poligalakturonat acid in the pectin bagasse to obtain the concentration of methanol to vary the enzyme crude extract PMEs. Concentration of crude enzyme extract PMEs used was 10%, 15%, 20% and 25% in 24-hour incubation with 2 repetitions performed. The resulting methanol levels were analyzed using GC (Gas Chromatography). The results of this study concluded that allowing the concentration used for hydrolysis of bagasse to produce methanol using crude enzyme from  Bacillus subtilis (PMEs) is 10% with a methanol content of 0.02%.